Opening the eyes: Children’s Drawing through the collection of alternative materials (Revista Apotheke, 2026)
This essay discusses a case study carried out in the course Artes Visuais e Grafismo Infantil (Visual Arts and Children’s Drawing), offered in the second semester of the Licenciatura em Artes Visuais (Visual Arts License Degree) at the Universidade do Estado de Santa Catarina (UDESC). Through a set of drawing propositions developed with a ten-year-old child, the text examines how different pedagogical approaches shape children’s graphic production, revealing shifts from the usual drawing schemas toward a more attentive process of observation and experimentation. The discussion is informed by two key concepts, collecting and pedagogical scene, understood as organizational practices that mediate the perception and aesthetic experience of materials, in dialogue with Cunha (2021), Silva (2017; 2022), Lima and Lampert (2023), and Albers (2006).
Keywords: children’s drawing; collection; pedagogical scene